Effect of the isotope mass on the turbulent transport at the edge of L-mode plasmas in ASDEX Upgrade and JET-ILW. (11th October 2019) - Bonanomi, N.; Angioni, C.; Crandall, P.C.; Di Siena, A.; Maggi, C.F.; Schneider, P.A.
Abstract: The nature of the turbulent transport in the edge region of ASDEX Upgrade and JET-ILW deuterium (D) and hydrogen (H) L-mode plasmas is studied using local gyro-kinetic simulations. For both devices the turbulence is found to be dominated by an electron drift-wave destabilized by the high collisionality in the plasma edge and strongly related to the kinetic electron dynamics. The isotope ion mass is found to have an important impact on the edge turbulence. In linear simulations, wider eigenfunctions of the electrostatic potential with a lower isotope mass translate in a lower threshold in the normalized electron temperature gradient and in a higher linear growth rate. In non-linear simulations, higher turbulent transport is predicted with a lower isotope mass. The effect of the isotope mass on the turbulent fluxes is enhanced by electromagnetic effects, which are found to be important in non-linear simulations. Remarkably, when considering all the effects in the non-linear simulations and the experimental uncertainties, the predicted fluxes can reproduce the experimental fluxes and their behavior with the isotope mass.